Alleviating the North Atlantic cold bias in the Kiel Climate Model - Drews, Annika; Greatbatch, Richard John; Ding, Hui; Latif, Mojib; Park, Wonsun (2015)
The North Atlantic cold bias, associated with a too zonal path of the North Atlantic Current and a missing “northwest corner”, is a major problem in coupled models. It affects the North Atlantic Sector climate mean state, variability and predictability, as this severe model error is located in the North Atlantic storm track region. In the standard model version of the Kiel Climate Model (KCM), like in many other climate models, the surface heat flux is reversed in the northwest corner; the ocean gains heat, instead of releasing heat to the atmosphere as observed. The use of a Flow Field Correction (FFC) to adjust the path of the North Atlantic Current is investigated as well as additional corrections to the surface heat and freshwater fluxes. The FFC can be regarded as a means to correct for model error, e.g. associated with the deep water mass pathways and their impact on the circulation, and to parameterize unresolved processes such as eddy momentum flux convergence. The FFC does not depend on the state of the coupled model. Results show that the FFC allows a northward flow into the northwest corner, largely eliminating the subsurface bias in the KCM. A cold bias remains at the surface but can be eliminated by additionally correcting the surface freshwater flux, without adjusting the surface heat flux seen by the ocean model. Sea ice and convection occurs in more realistic positions in the corrected model versions, connected to a more northward extension of the Atlantic Meridional Overturning Circulation (AMOC). Using the corrected model versions, we explore the North Atlantic region climate variability with a focus on the AMOC and basin-wide North Atlantic sea surface temperature variability known as the Atlantic Multidecadal Oscillation or Variability (AMO/V).